2015
DOI: 10.1177/0960327115572706
|View full text |Cite
|
Sign up to set email alerts
|

High dosage of monosodium glutamate causes deficits of the motor coordination and the number of cerebellar Purkinje cells of rats

Abstract: Monosodium glutamate (MSG) has been widely used throughout the world as a flavoring agent of food. However, MSG at certain dosages is also thought to cause damage to many organs, including cerebellum. This study aimed at investigating the effects of different doses of MSG on the motor coordination and the number of Purkinje cells of the cerebellum of Wistar rats. A total of 24 male rats aged 4 to 5 weeks were divided into four groups, namely, control (C), T2.5, T3, and T3.5 groups, which received intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(75 reference statements)
0
15
0
2
Order By: Relevance
“…Between P4 and P10, animals were weighed and injected (subcutaneously, along the dorsal hindquarters) with MSG (4 mg/g) or saline (equivalent volume of 0.9% NaCl). This dosage of MSG has been shown previously to produce robust effects in the hippocampus and cerebellum [14,37]. Litters were weaned at P21 and the two cohorts (saline and MSG) were housed separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between P4 and P10, animals were weighed and injected (subcutaneously, along the dorsal hindquarters) with MSG (4 mg/g) or saline (equivalent volume of 0.9% NaCl). This dosage of MSG has been shown previously to produce robust effects in the hippocampus and cerebellum [14,37]. Litters were weaned at P21 and the two cohorts (saline and MSG) were housed separately.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, repeated exposure to MSG, especially during the neonatal period, results in neuronal damage and cell death in a number of different brain regions [2,4,8,35,38]. Specifically, MSG exposure has been shown to result in fewer neurons in the spiral ganglion [5], severe degeneration of retinal ganglion cells [39,47], smaller brains and lower body weights [46], fewer cerebellar Purkinje cells, deficits in motor coordination [26,37] and fewer cortical neurons [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the respondents appeared to have little understanding of MSG and they were not frequent consumers of MSG. In addition, some of them did not know or had never heard of the term "monosodium glutamate (MSG)" [22]. It is commonly used by the Chinese but they do not use the term MSG and that may be the reason they were not aware of it, even though it is marketed in brands that they are familiar with [23].…”
Section: Resultsmentioning
confidence: 99%
“…Values in each column followed by * are significantly different (P ≤ 0.05), and that followed by ** are highly significantly different (P ≤ 0.001) Fig. 4 Calibration curve of sodium glutamate obtained by the proposed HPLC method Prastiwi et al, 2015 found that the administration of MSG at a high dose of 3.5 mg/g body weight, but not at lower dosages, lead to significant decrease of motor coordination and the estimated total number of Purkinje cells of rats and significant correlation between motor coordination and the total number of Purkinje cells (Prastiwi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%